2018
DOI: 10.1136/archdischild-2018-314807
|View full text |Cite
|
Sign up to set email alerts
|

Early warning scores in paediatrics: an overview

Abstract: Paediatric Early Warning Scores (PEWS)are used in hospitalised patients to detect physiological deterioration and is being used increasingly throughout healthcare systems with a limited evidence based. There are two versions in general use that can lead to a clinical response, either by triggering an action or by reaching a ‘threshold’ when graduated responses may occur depending on the value of the score. Most evidence has come from research based on paediatric inpatients in specialist children’s hospitals, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 44 publications
0
50
0
11
Order By: Relevance
“…Sambeeck et al in a cross-sectional survey revealed that the use of 45 different EWS scores in Dutch hospitals can lead to a false sense of security and recommended to establish a national working group to coordinate implementation of an EWS usable for both general and university hospitals 34. A recent review emphasised that despite widespread use, the evidence base for EWS remains limited because there is no consensus of the most effective EWS and there exists a lack of robust, valid and clinically meaningful outcomes 35. In the evaluating processes of care and outcomes of children in hospital (EPOCH) Randomised Clinical Trial, including 144 539 patients, the effect of the Bedside PEWS intervention was assessed on all-cause hospital mortality and late admission to PICU, cardiac arrest and ICU resource use.…”
Section: Discussionmentioning
confidence: 99%
“…Sambeeck et al in a cross-sectional survey revealed that the use of 45 different EWS scores in Dutch hospitals can lead to a false sense of security and recommended to establish a national working group to coordinate implementation of an EWS usable for both general and university hospitals 34. A recent review emphasised that despite widespread use, the evidence base for EWS remains limited because there is no consensus of the most effective EWS and there exists a lack of robust, valid and clinically meaningful outcomes 35. In the evaluating processes of care and outcomes of children in hospital (EPOCH) Randomised Clinical Trial, including 144 539 patients, the effect of the Bedside PEWS intervention was assessed on all-cause hospital mortality and late admission to PICU, cardiac arrest and ICU resource use.…”
Section: Discussionmentioning
confidence: 99%
“…Предотвращение неблагоприятных событий является одним из резервов повышения эффективности стационарного лечения. Раннему выявлению факторов риска развития неблагоприятных событий способствуют системы раннего предупреждения (Pediatric Early Warning Score, PEWS), которые основаны на периодической регистрации витальных показателей пациентов и вычисления суммы частоты их отклонений от референсных значений [2]. Различные модификации систем раннего предупреждения учитывают частоту сердечных сокращений (ЧСС), частоту дыхания (ЧД), температуру тела, систолическое (САД) и диастолическое (ДАД) артериальное давление, уровень сатурации кислородом пульсирующей артериальной крови (SpO 2 ) [3].…”
Section: обоснованиеunclassified
“…Frequency of vitals deviations from reference ranges at admission to intensive care unit Примечание. 1 -референсный интервал по [8], 2 -референсный интервал по [11]. -ниже референсного предела, -выше референсного предела.…”
Section: ограничения исследованияunclassified
See 1 more Smart Citation
“…However, although mortality trends have been shown to diminish over time, 1 the evidence base supporting their impact has often been quite heterogeneous. 2,3 In particular, a recent international randomized control trial of a PEWS approach was found not to improve overall mortality. 4 A major challenge with the evaluation of these patient safety systems is the reliance on mortality as an outcome measure.…”
mentioning
confidence: 99%